1999
DOI: 10.1023/a:1018713115866
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Gender constancy judgments in children referred for problems in their gender identity development (N = 206) and controls (N = 95) were compared. On Slaby and Frey's (1975) gender constancy interview, the gender-referred children performed more poorly than the controls at three stage levels: gender identity, gender stability, and gender consistency. On the Boy-Girl Identity Task, a second measure of gender constancy (Emmerich et al., 1977), the gender-referred children also performed more poorly. Gender-referre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 78 publications
1
21
0
Order By: Relevance
“…For example, the clinic-referred children preferred playmates, toys, and play styles associated stereotypically with the opposite sex more often than their same-sex peers (31)(32)(33)(34)(35)(36), like the socially transitioned transgender children in the TYP (in fact, the TYP children showed effects that were equal in magnitude to opposite-sex gender-typical peers; 6, 7). The children in the older studies also endorsed beliefs about gender stability at lower levels than gender-typical children in the control group, consistent with findings related to transgender children who have transitioned socially (37). While many of the findings from these past and current studies are similar, one striking dissimilarity involves a measure of gender identity.…”
Section: Limits Related Research and Next Stepssupporting
confidence: 70%
See 1 more Smart Citation
“…For example, the clinic-referred children preferred playmates, toys, and play styles associated stereotypically with the opposite sex more often than their same-sex peers (31)(32)(33)(34)(35)(36), like the socially transitioned transgender children in the TYP (in fact, the TYP children showed effects that were equal in magnitude to opposite-sex gender-typical peers; 6, 7). The children in the older studies also endorsed beliefs about gender stability at lower levels than gender-typical children in the control group, consistent with findings related to transgender children who have transitioned socially (37). While many of the findings from these past and current studies are similar, one striking dissimilarity involves a measure of gender identity.…”
Section: Limits Related Research and Next Stepssupporting
confidence: 70%
“…While many of the findings from these past and current studies are similar, one striking dissimilarity involves a measure of gender identity. Fewer than 10% of children in the older studies identified as the gender opposite their sex at birth when asked if they were boys or girls (37,38). This contrasts with most children in the TYP, who report being a member of the gender group opposite their sex at birth.…”
Section: Limits Related Research and Next Stepsmentioning
confidence: 83%
“…Children are not said to understand gender until they understand these "facts" (e.g., Kohlberg, 1966)-yet the scientific and political understanding of the truth of these claims is changing. We now know that there are people whose gender is in fact different than their sex, we now know that there are some people whose gender changes during the course of their development, and we know that there are people who are neither male nor female by standard criteria, yet our studies require that children endorse these empirically false claims about gender and sex to be granted the "correct" understanding of gender (e.g., Zucker et al, 1999). Imagine, for example, a child who personally knows a transgender childwould he or she be wrong to state that a child's sex and gender can diverge?…”
Section: Gender and Sex-diverse Individuals As Targets Of Social Percmentioning
confidence: 96%
“…and assuming that understanding gender is synonymous with an answer that aligns with one's sex at birth (Zucker & VanderLaan, 2016). Further, those who deviate from normative views on these items (e.g., transgender children) are thought to show a cognitive deficiency or delay (e.g., Zucker et al, 1999). Thus, by focusing on the most prototypical members of groups, the field may be overstating or oversimplifying our theories about social categorization in early childhood.…”
Section: Why Go Beyond the Discrete?mentioning
confidence: 99%
See 1 more Smart Citation